Unique genetic features of canine adenovirus type 1 (CAdV-1) infecting red foxes (Vulpes vulpes) in northern Norway and arctic foxes (Vulpes lagopus) in Svalbard - Balboni, Andrea; Tryland, Morten; Mørk, Torill; Killengreen, Siw Turid; Fuglei, Eva; Battilani, Mara (Veterinary Research Communications, 2019)
This is a post-peer-review, pre-copyedit version of an article published in Veterinary Research Communications. The final authenticated version is available online at: https://doi.org/10.1007/s11259-019-09746-y Canine adenovirus type 1 (CAdV-1) is the aetiological agent of infectious canine hepatitis (ICH) in domestic dogs ( Canis familiaris ). In spite of the widespread use of vaccination, CAdV-1 continues to circulate in the dog population. Although a high number of serological screenings have indicated that CAdV-1 is widespread in fox species, little is known about the potential role of foxes as reservoirs of CAdV-1. Furthermore, very little data exist on the molecular features of this virus in foxes. To add to existing knowledge on CAdV-1 circulating in wild carnivores, tissue samples from CAdV-seropositive red foxes ( Vulpes vulpes, n = 10) from the northern mainland of Norway and arctic foxes ( Vulpes lagopus, n = 10) from the Svalbard archipelago, Norway, were investigated using a molecular approach to detect CAdV-1 DNA and important structural and non-structural genes of the detected viruses were sequenced and analysed. Amplicons characteristic for CAdV-1 were amplified from 14 out of 20 foxes (7 red foxes and 7 arctic foxes) and spleen and lymph node tissues resulted optimal targets for the viral DNA detection. The nucleotide sequences showed unique features that distinguished the viruses detected in this study from the CAdV-1 to date identified in wild carnivores and dogs. Greater attention should be given to genetically different CAdV-1 circulating in wild carnivores that may be transferred to dogs, potentially causing disease and reducing the effectiveness of available vaccines.